An Experimental Study of Human and Artificial Intelligence Collaboration in TikTok Advertising: Effects on Audience Perception and Engagement - Kasyfan, Nadhif Muhammad; Purwaamijaya, Btari Mariska; Ar Ridlo, Muhammad Dzikri (SAINTIS Publishing, 2025)
The use of generative artificial intelligence, or GenAI in short form video advertising, continues to grow due to its efficiency and scalability. However, questions remain regarding audience acceptance, perceived authenticity, and the effectiveness of AI-generated advertising on social media platforms such as TikTok. This study examines how different creative configurations, namely Human Only, AI Only, and Human-AI Collaboration, influence audience perception and engagement in TikTok advertising. This study employed an experimental mixed methods approach. Quantitatively, two sequential A B split tests were conducted using TikTok Ads Manager to compare Human Only versus AI Only advertising and Human Only versus Human-AI Collaboration advertising. Audience engagement was measured using Completion Rate as the primary indicator and six-second view rate as a secondary indicator. Qualitatively, in-depth interviews with active TikTok users were conducted to examine audience processing mechanisms based on the Elaboration Likelihood Model. The results show that Human Only advertising achieved higher completion rates and early engagement than AI Only advertising. Furthermore, Human-AI Collaboration generated the highest engagement compared to Human-Only advertising. Qualitative findings indicate that human involvement strengthens perceived authenticity and trust, while AI supports visual structure that sustains attention and message elaboration. In conclusion, Human-AI Collaboration represents the most effective and socially acceptable approach to short-form video advertising, with implications for digital advertising strategy, ethical AI use, and the sustainable integration of generative technologies in social media communication.